2017
DOI: 10.1007/s10118-017-1932-7
|View full text |Cite
|
Sign up to set email alerts
|

Poly(β-cyclodextrin)-mediated polylactide-cholesterol stereocomplex micelles for controlled drug delivery

Abstract: A series of host-guest interaction-adjusted polylactide stereocomplex micelles was prepared via the self-assembly of 4-armed poly(ethylene glycol)-block-poly(L-lactide/D-lactide)-cholesterol (4-armed PEG-b-PLLA/PDLA-CHOL) and poly(β-cyclodextrin) (PCD) with the molar ratios of CHOL/β-CD at 1 : 0.5, 1 : 1, and 1 : 2 in an aqueous environment. The hydrodynamic diameters of the micelles ranged from 84.1 nm to 107 nm depending on the molar ratio of CHOL/β-CD. It was shown that the micelle with the largest proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 18 publications
0
43
0
Order By: Relevance
“…To reduce the toxicity associated with ZnO NM exposure, it may be necessary to use surface coating to change the interactions between ZnO NMs and cells (Cao et al, ; Liu et al, ), or use NMs based on biocompatible materials other than ZnO for biomedical purposes (An & Zhang, ; Wang et al, ). Alternatively, targeted drug delivery to realize accumulation of toxic ZnO NMs at specific sites could also be considered (Cai et al, ; Feng, Ding, Gref, & Shen, ; Shi et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the toxicity associated with ZnO NM exposure, it may be necessary to use surface coating to change the interactions between ZnO NMs and cells (Cao et al, ; Liu et al, ), or use NMs based on biocompatible materials other than ZnO for biomedical purposes (An & Zhang, ; Wang et al, ). Alternatively, targeted drug delivery to realize accumulation of toxic ZnO NMs at specific sites could also be considered (Cai et al, ; Feng, Ding, Gref, & Shen, ; Shi et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] As well, antitumor activity of doxorubicin has been considerably enhanced through different micellar nanoparticles. [31][32][33] Pluronics represent a class of block copolymers formed of hydrophilic blocks of poly(ethylene oxide) (PEO) and hydrophobic poly(propylene oxide) (PPO) in tri-block arrangement of PEO-PPO-PEO ( Figure 1B). 34 Pluronics form micelles with a hydrophobic PPO core within …”
mentioning
confidence: 99%
“…In the case of high molecular weight PLA, the stereocomplex melting point is about 50 °C higher (230 °C) than that of the PLLA or PDLA homopolymers (180 °C), and the melting enthalpy value reported in the literature (reflecting polymer crystallinity) for 100% crystalline stereocomplex prepared from high molecular weight PLA is 142 J g −1 (145 J g −1 by other authors) whereas one of the reported melting enthalpies of PLLA homocrystallites is 93 J g −1 . The stabilization of PLA‐based micelles (PLA/poly(ethylene oxide) or PLA with other hydrophilic block copolymers) by the introduction of PLA stereocomplex into the micelle structure has been applied by many authors and this type of stereocomplex implementation dominates . Apart from micelles formed in a water medium, different solid (nano)microparticles based on PLLA and PDLA copolymers were also prepared by the application of such methods as solvent evaporation, precipitation, lowering solvent temperature or spray droplet atomization .…”
Section: Introductionmentioning
confidence: 95%